PERADILAN TATA USAHA NEGARA INDONESIA SUATU PEMIKIRAN KE ARAH PERLUASAN KOMPETENSI PASCA AMANDEMEN KEDUA UNDANG-UNDANG PERADILAN TATA USAHA NEGARA - Effendi, Maftuh (Jurnal Hukum dan Peradilan, 2014)
Indonesian administrative courtsâ€™ absolute jurisdiction are limited to the administrative decisions. It leads the courts as a special administrative court, even a â€œvery special courtâ€, because such definition of administrative decisions laid down on Law on Administrative Court is more narrow compared to the definition of administrative decision as laid down on the General Administrative Law Act of the Netherlands as it source. Most court decisions on the courtsâ€™ absolute jurisdiction vary in interpretations that make them unpredictable. They cause uncertainty and inconsistency in the application of administrative courtsâ€™ absolute jurisdiction. Furthermore, they create confusion to the society looking for appropriate forum dealing with administrative acts and bafflement to the administrations executing courtsâ€™ decisions. The concept offered to the expansion of Indonesian administrative courtsâ€™ absolute jurisdiction are based on the method and determination of administrative disputes. Method used is general method, while determination used is subjective and objective determinations. Subjective determination includes external and internal disputes, while objective determination includes all administrative acts in the field of public laws covered the legal and factual acts causing material or immaterial damages. Keywords: administrative courts, absolute jurisdiction, expansion.